2018
DOI: 10.3390/app8081286
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Decomposition and Convolutional LSTM Networks Based Improved Deep Learning Model for Solar Irradiance Forecasting

Abstract: Solar photovoltaic (PV) power forecasting has become an important issue with regard to the power grid in terms of the effective integration of large-scale PV plants. As the main influence factor of PV power generation, solar irradiance and its accurate forecasting are the prerequisite for solar PV power forecasting. However, previous forecasting approaches using manual feature extraction (MFE), traditional modeling and single deep learning (DL) models could not satisfy the performance requirements in partial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 50 publications
0
80
0
Order By: Relevance
“…These models are similar to ones mentioned in previous studies [26,41], but the LSTM-based model proposed in this study has a significant difference because it attempts to estimate hourly PV power output regardless for meteorological conditions and considering meteorological and seasonal trends. In addition, while some models attempt to predict solar radiation [42][43][44] rather than PV power output prediction, our study focuses on the direct estimation of PV power output.…”
Section: Introductionmentioning
confidence: 99%
“…These models are similar to ones mentioned in previous studies [26,41], but the LSTM-based model proposed in this study has a significant difference because it attempts to estimate hourly PV power output regardless for meteorological conditions and considering meteorological and seasonal trends. In addition, while some models attempt to predict solar radiation [42][43][44] rather than PV power output prediction, our study focuses on the direct estimation of PV power output.…”
Section: Introductionmentioning
confidence: 99%
“…As the main influence factor of PV power generation, the solar irradiance and its accurate forecasting are prerequisites for solar PV power forecasting. Authors in [24] proposed an improved LSTM model to enhance the accuracy of day-ahead solar irradiance forecasting, and the simulation results indicated that the proposed model has high superiority in the solar irradiance forecasting, especially under extreme weather conditions. A new method for 1-h-ahead PV power forecasting using deep LSTM networks was proposed [25], which can capture abstract concepts in the PV power sequences.…”
Section: Introductionmentioning
confidence: 99%
“…To test the prediction effect of the model proposed in this paper, we compared the results of the following prediction models: (1) the single prediction models (ARMA, DBN) used in this paper; (2) the common neural network prediction model, RNN and Gradient Boost Decision Tree (GBDT) in literature [46] and [47], used on a representative basis; (3) the combined prediction model, Discrete Wavelet Transformation (DWT) in literature [48] and traditional EMD and EEMD are used on a representative basis. The prediction results for each model are shown in Figure 11.…”
Section: Discussion and Comparisonmentioning
confidence: 99%